Urban layout and energy savings - Wojciech Skórzewski (Acta Scientiarum Polonorum. Architectura)
In the era of climate changes, one of the most important challenges of architectural designing is a reduction of energy consumption in buildings for heating and cooling purposes. A significant component of the energy balance of buildings is passive solar heat gains, the amount of which depends, among other things, on the mutual location of buildings. The article discusses the preliminary research on the possibilities of achieving energy savings of buildings at the stage of urban design in Polish legal and climatic conditions. The study includes the analysis of several variants of the layout of buildings located at the same plot.